Relationship between the shooting success rate and match result in soccer at the FIFA World Cup 2018 - Holienka, M.; Nagy, N.; Basa, R.; Babic, M. (Journal of Physical Education and Sport, 2020)
The success rate of individual game activities is one of the main indicators of individual game performance. The aim of our research was to point out the relationship between shooting success rate of the selected offensive individual game activity - shooting at the FIFA World Cup 2018 and the final result in the match. We assumed a statistically significant relationship between the shooting success rate and the result in semi-finalists matches. To obtain the required data was used the indirect observation method. We observed 23 matches of semi-finalists at the FIFA World Cup 2018. The frequency and success rate of this selected offensive individual game activity were written down in record sheets prepared in advance and these data were processed and evaluated based on mathematical-statistical methods. To determine the relationship between the shooting success rate and the final result in the match, we used a statistical method for the relationship analysis called the Chi-Squared Test. The results showed that the relationship between the shooting success rate and the final match result was not statistically significant (p> 0.05). In terms of the entire team, when speaking about the final result, the success rate of the final offensive individual game activity can be a significant indicator of the team ´s success in a match. The higher is the shooting success rate, the higher is the chance to score a goal, and so be successful in the match.